2013
DOI: 10.1364/oe.21.012942
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of fiber lasers with long and ultra-long ring cavity

Abstract: We highlight two important aspects related to a mathematical modeling of pulsed fiber lasers with long and ultra-long ring cavity -impact of an initial noise and a cavity length on generation of single optical pulses. Using as an example a simple scalar model of a ring fiber laser that describes the radiation build-up from noise and the following intra-cavity pulse dynamics during a round trip we study dependence of generated pulse characteristics on the resonator length in the range from 30 m up to 2 km.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 32 publications
(72 reference statements)
1
27
0
1
Order By: Relevance
“…However, fiber lasers offer another important degree of freedom that can be used for designing novel generation regimes: resonator length. As was demonstrated by multiple groups [25][26][27][28][29][30][31][32][33], the cavity length has a substantial impact on the output pulse parameters in mode-locked fiber lasers. Specifically, it is possible to control the pulse energy and repetition rate by changing the laser cavity.…”
Section: Ultra-long Mode-locked Fiber Lasers: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, fiber lasers offer another important degree of freedom that can be used for designing novel generation regimes: resonator length. As was demonstrated by multiple groups [25][26][27][28][29][30][31][32][33], the cavity length has a substantial impact on the output pulse parameters in mode-locked fiber lasers. Specifically, it is possible to control the pulse energy and repetition rate by changing the laser cavity.…”
Section: Ultra-long Mode-locked Fiber Lasers: Discussionmentioning
confidence: 98%
“…It was experimentally and theoretically confirmed that passively mode-locked fiber master oscillators give rise to a broad variety of generation regimes in different cavity configurations [46][47][48][49][50][51][52][53], including generation of single and multiple pulses over a cavity round-trip, pulses with various duration, envelope shape, and spectrum width. The results of Refs [30,52] show that in ultra-long lasers, there is high probability of generating double-scale partially coherent pulses, whereas ''normal'' (single-scale) pulses with a smooth temporal optical phase shape and large chirp become difficult to obtain. This indicates a step difference from the traditional mode-locking theory and may be considered as a partial mode-locking, when phase locking is not between all resonator modes, but rather between groups/clusters of modes.…”
Section: Ultra-long Mode-locked Fiber Lasers: Discussionmentioning
confidence: 99%
“…As it has been shown that the simulated steady-state is influenced by the form of the initial seed field in some cases (e.g. lasers with long cavities [147]), here we choose to seed stochastically using a one-photonper-mode shot noise model, analogous to real-world experimental systems. Propagation in fibre is described by a generalised nonlinear Schrödinger equation (similar to the formalism of Ref.…”
Section: Appendix: Numerical Modelling Methodsmentioning
confidence: 99%
“…38 Moreover, our results for the parabolic shape of the pulse and the behavior of the laser pulse propagation through the fiber laser exhibit good agreement with previous studies. [39][40][41][42][43] …”
Section: Discussionmentioning
confidence: 99%